Efectividad de la terapia cognitivo conductual para la ansiedad en adolescentes con trastorno del espectro autista - Bustamante Calle, Andrea Maria (2024)
Anxiety is a common concern among adolescents with Autism Spectrum Disorder (ASD), being one of the most prevalent conditions. This study aims to determine if Cognitive Behavioral Therapy (CBT) is an effective option for addressing anxiety in this group. To do so, a systematic search was conducted following the PRISMA guidelines (Page et al., 2021), consulting databases such as Scopus, Web of Science, and Scielo. Ten studies were included in the analysis, which evaluated different intervention programs of CBT, especially in clinical settings. Of these, eight concluded that CBT is effective in reducing anxiety in adolescents with ASD, while two did not find clear evidence of its effectiveness, noting a somewhat insignificant decrease in anxious symptoms. All studies compared anxiety measures before and after the intervention. It is suggested that future research focus on adapting CBT specifically for individuals within the autism spectrum, as it has shown to be effective in clinical contexts.